Rhetorical stylistics of Rashid al-Din Fadlullah Hamedani's Letters (The Stories of Thoughts) - Tahereh Ishany (مطالعات زبانی و بلاغی)
One of the methods of stylistics with a critical approach is layered stylistics. Layered stylistics is a practical tool through which to receive hidden meanings in any work that is wrapped in an envelope of text superstructure and is not easily received; By examining and analyzing linguistic objectivity, it is possible to reach the ideology and discourse governing the text. On the other hand, the examination of letters is important from the point of view that they express the culture of every nation at any time and in any place; Because in addition to the fact that letters are written with special purposes; Line by line also has a meaning and conveys an idea from the writer of the letter. Rashid al-Din Fadlullah Wazir, a scholar of the Mongol period with a powerful pen, is the writer of Letters, titled The Stories of Thoughts (Savāneh-Al Afkār), which clearly indicates his knowledge of literary techniques and devices. So far, the work has not been investigated from the perspective of layered stylistics and, precisely speaking, rhetorical stylistics. Layered stylistics is a practical tool to perceive the text undercurrent of meaning and the ideology and discourse governing the text. In the rhetorical approach to layered stylistics, the text is investigated from the viewpoint of structural and interpersonal rhetoric as well the application of figurative language. This descriptive analytical research of Rashid al-Din's Letters seeks to answer the following questions: Regarding the rhetorical layer, what are the stylistic features of the work? What functions do these features serve in relation to their context?  What power relation between the author and the addresses are revealed through these features? In the stylistic examination of Letters and in response to the aforementioned questions, the position of the audience as well as the powerful position of the writer of Letters were identified as factors affecting the structural rhetoric of the work. More than half of the letters, addressed to the governmental addressees, are written without an introduction. This indicates the insignificance of this type of audience from the writer's point of view and his superior position of authority, as a result of which he did not consider himself bound to observe the principles governing letter writing in order to attract the attention of this type of audience. Meanwhile, in the letters addressed to friends, introduction and necessary background are provided and the text is written observing all the principles of letter writing of his era. In terms of interpersonal rhetoric, although Rashid al-Din chooses various methods to establish fruitful communication between himself and the audience; his use of the "imperative approach" as the dominant method confirms his authoritative position vis-à-vis the audience of the letters. Also, the frequent use of the two rhetorical devices of simile and metaphor indicates his power of literary image creation, as a tool in many cases in line with the ideology governing the text and its injection to the audience of the letters. According to the results of this research, it can be said that Rashid al-din's relationship with most of the audience is from the superior position of power; he makes effective use of language facilities, in addition to using ideological similes and metaphors, to strengthen his political and cultural purposes and to have his order or desire carried out.